Metagenomic search strategies for interactions among plants and multiple microbes - Melcher, Ulrich; Verma, Ruchi; Schneider, William L. (Frontiers in Plant Science, 2014)
Plants harbor multiple microbes. Metagenomics can facilitate understanding of the significance, for the plant, of the microbes and of the interactions among them. However, current approaches to metagenomic analysis of plants are computationally time-consuming. Efforts to speed the discovery process include improvement of computational speed, condensing the sequencing reads into smaller datasets before BLAST searches, simplifying the target database of BLAST searches, and flipping the roles of metagenomic and reference datasets. The latter is exemplified by the E-probe diagnostic nucleic acid analysis (EDNA) approach originally devised for improving analysis during plant quarantine.